2018
DOI: 10.1111/bjet.12625
|View full text |Cite
|
Sign up to set email alerts
|

A framework for applying learning analytics in serious games for people with intellectual disabilities

Abstract: This paper proposes a systematic framework to integrate learning analytics into serious games for people with intellectual disabilities. Serious games for an inclusive learning environment need to be prudently designed with adaptive and measurable competencies to meet the needs of the target users. The recent emergence of learning analytics provides a capability to capture important data in real time from within the highly interactive nature of serious games to better understand and enhance the learning proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 36 publications
0
18
0
1
Order By: Relevance
“…A framework involving three major components, i.e., learner profiling, learning adaptation, and learning evaluation, was designed for disabled people to engage in learning process by integrating learning analytics into serious games, which could be meaningful for the design, implementation, evaluation, and adaptation of serious games for education [26]. Serious game assisted learning also proved effective in learning for those caught with autism spectrum disorders.…”
Section: Use Of Serious Gaming In Medical Educationmentioning
confidence: 99%
“…A framework involving three major components, i.e., learner profiling, learning adaptation, and learning evaluation, was designed for disabled people to engage in learning process by integrating learning analytics into serious games, which could be meaningful for the design, implementation, evaluation, and adaptation of serious games for education [26]. Serious game assisted learning also proved effective in learning for those caught with autism spectrum disorders.…”
Section: Use Of Serious Gaming In Medical Educationmentioning
confidence: 99%
“…Previous research has shown that adults, young people, and children are motivated by serious games (Girard, Ecalle, & Magnan, 2013;Mayer, 2016), which can be effective tools for developing our cognitive skills (De la Guía et al, 2015;Jackson, Brummel, Pollet, & Greer, 2013;Nguyen, Gardner, & Sheridan, 2018). To achieve learning goals, games have to be planned to balance learning and fun (Lameras et al, 2017).…”
Section: Learning Processmentioning
confidence: 99%
“…(Fessakis, Gouli, & Mavroudi, 2013). Because children have different abilities and needs, games should be flexible and adapted to help them face new challenges (M.9) (Nguyen et al, 2018). Some mediation categories have been detected through the difficulties in the game process.…”
Section: Mediation Guidelinesmentioning
confidence: 99%
“…Previous research has addressed different applications of learning analytics in serious games. However, few research studies have investigated the needs of individuals with cognitive disabilities [17]. The work of [18] reviewed the effects of serious games on people with intellectual disabilities or autism spectrum disorder and found that games had a positive impact on the players.…”
Section: Related Workmentioning
confidence: 99%